Major Trends in Public Health Law and Practice: A Network National Report. Issue 3 (1st October 2013) - Hodge, James G.; Barraza, Leila; Bernstein, Jennifer; Chu, Courtney; Collmer, Veda; Davis, Corey; Griest, Megan M.; Hammer, Monica S.; Krueger, Jill; Lowrey, Kerri McGowan; Orenstein, Daniel G.
<x xml:space="preserve">Abstract</x> Since its inception in September 2010, the Network for Public Health Law has responded to hundreds of public health legal technical assistance claims from around the country. Based on a review of these data, a series of major trends in public health practice and the law are analyzed, including issues concerning: the Affordable Care Act, tobacco control, emergency legal preparedness, health information privacy, food policy, vaccination, drug overdose prevention, sports injury law, public health accreditation, and maternal breastfeeding. These and other emerging themes in public health law demonstrate the essential role of law and practice in advancing the public's health.